2016
DOI: 10.1111/1744-1633.12168
|View full text |Cite
|
Sign up to set email alerts
|

Implement of Palatoplasty Enhanced Recovery (PER) pathway for cleft palate repair after the audit from the Surgical Outcomes Monitoring and Improvement Program (SOMIP)

Abstract: Aim: Length of stay (LOS) is an important outcome measure of the Surgical Outcomes Monitoring and Improvement Program (SOMIP). After analyzing the outcomes of the first two SOMIP reports, we introduced the Palatoplasty Enhanced Recovery (PER) pathway for primary cleft palate repair in 2012. We aim to study if the implementation of PER pathway can decrease the LOS without increasing the complication rate. Methods: All children who underwent primary cleft palate repair from January 2008 to April 2015 were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Three studies (50%) reported on the rate of postoperative complications to assess patient safety (Supplementary Table 4). 13,15,20 There were no apparent differences in complication rates between cohorts across studies. However, the broad descriptions of complications between studies rendered pooled analysis unfeasible.…”
Section: Patient Safetymentioning
confidence: 87%
See 3 more Smart Citations
“…Three studies (50%) reported on the rate of postoperative complications to assess patient safety (Supplementary Table 4). 13,15,20 There were no apparent differences in complication rates between cohorts across studies. However, the broad descriptions of complications between studies rendered pooled analysis unfeasible.…”
Section: Patient Safetymentioning
confidence: 87%
“…Ultimately, we included 6 studies for qualitative synthesis and 5 studies for quantitative synthesis (Table 1). 13,15,[19][20][21][22]…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Following screening, 18 articles underwent full-text review and 5 studies [14][15][16][17][18] met final inclusion criteria. Upon initial review, 1 study was found to deliberately compare outcomes between controls and an ERAS group that was distinctly different with regards to demographics and medical history.…”
Section: Studies and Patientsmentioning
confidence: 99%